Ethnic Party Bans in East Africa from a Comparative Perspective - Anika Moroff (German Institute of Global and Area Studies (GIGA), 2010)
Since 1990 the banning of ethnic and other identity-based parties has become the norm in sub-Saharan Africa. This article focuses on Kenya, Tanzania and Uganda as three East African countries that have opted for different ways of dealing with such parties. Using case studies, it traces the origins of the party bans in Tanzania and Uganda and explores the reasons for the absence of a ban in Kenya. The analysis shows that the laws on particularistic parties have actually been implemented by the appropriate institutions. However, these laws have only marginally influenced the character of the political parties in the three countries: A comparison of regional voting patterns suggests that bans on particularistic parties have not ensured the emergence of aggregative parties with a national following in Tanzania and Uganda. In Kenya on the other hand, where such a ban was nonexistent until 2008, parties have not proven to be more regional. – – Das Verbot ethnischer und anderer identitätsbasierter politischer Parteien ist seit Beginn der 1990er Jahre im subsaharischen Afrika zur Norm geworden. Der vorliegende Aufsatz analysiert drei ostafrikanische Länder, die verschiedene Wege im Umgang mit partikularistischen Parteien eingeschlagen haben und untersucht, warum Tansania und Uganda ein Parteienverbot eingeführt haben, Kenia jedoch nicht. Die Untersuchung macht zudem deutlich, dass die zuständigen Institutionen die Gesetze zwar anwenden, dies jedoch nicht zu nationalen Parteien führt: Eine Analyse der Wahlergebnisse auf subnationaler Ebene zeigt, dass insbesondere Oppositionsparteien oft regionale Hochburgen aber keine landesweite Unterstützung haben. Politische Parteien in Kenia sind dabei trotz divergierender Parteiregulierung nicht deutlich weniger national als Parteien in Tansania und Uganda.
Keywords: 300; Sub-Saharan Africa; party ban; ethnic parties; Kenya; Tanzania; Uganda; party regulation; party nationalization